Virulent and attenuated strains of Trichoderma citrinoviride mediated resistance and biological control mechanism in tomato - Zhao, Di; Shen, Dan; Fan, Haiyan; Zhu, Xiaofeng; Wang, Yuanyuan; Duan, Yuxi; Chen, Lijie (Frontiers in Plant Science, 2023)
Introduction Root-knot nematode disease is one of the world's most serious vegetable crop diseases. In recent years, Trichoderma spp. has been widely used in root-knot nematode disease control as a biological control agent. Methods Virulent and attenuated strains of Trichoderma citrinoviride mediated resistance and biological control mechanism in tomato were determined. Results Preliminary experiments found differences in nematicidal virulence among Trichoderma citrinoviride. The 24-hour corrected mortality rate of the virulent strainT1910 was as high as 92.37%, with an LC50 of 0.5585 against the second juveniles (J2s) of Meloidogyne incognita. And the attenuated strain TC9 was 23.01%, the LC50 was 2.0615, so the virulent strain T1910 had a more substantial effect on the J2s than the attenuated strain. We found that the strong virulent strain T1910 have a good control effect on M. incognita by the pot experiment of tomato than that of the attenuated virulent strain TC9,especially the J2 and J4 numbers were inhibited inside the root knots of tomato. Theinhibition rates of virulent strains reached 85.22% and 76.91%, followed by attenuatedstrain TC9, which were 63.16% and 59.17%, respectively. To reveal the differences intomato defense pathways induced by different virulent strains, qRT-PCR was further usedto detect changes in the expression of inducement-related genes. The results showed thatthe TC9 was significantly upregulated at 5dpi, LOX1, PR1, and PDF1.2. The PR5 gene ofthe virulent strain T1910 was highly upregulated, and the JA pathway was activated laterbut weaker than the attenuated strain. The results of this study revealed that thebiocontrol mechanism of T. citrinoviride as poison killing through the virulent strain T1910 and induced resistance to M. incognita through attenuated strain, although virulence degradation also has an induced resistance effect. Moreover, the attenuated strain TC9 stimulated tomato immune response earlier than the virulent strain by nematode-associated molecular pattern-triggered (NAMP). Discussion Therefore, the research elucidated the mechanism of multiple control of Trichoderma spp. against M. incognita.